2020
DOI: 10.1111/jen.12825
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Ooencyrtus kuvanae (Hymenoptera: Encyrtidae) on two host species, Halyomorpha halys and Philosamia ricini

Abstract: Halyomorpha halys (Stål), the brown marmorated stink bug, is an invasive pentatomid species native to Asian countries (Hamilton et al., 2018).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Our results show that the parasitism rate increased with parasitoid age and number. Tunca et al [51] evaluated the potential of O. kuvanae as a biocontrol agent for H. halys and observed that the highest parasitism rate occurred by 5 and 7-day-old parasitoids. In a study by Aung et al [52], the percentage parasitism and the number of progeny of O. nezarae when parasitising eggs of R. clavatus were significantly decreased in old females (20 days old).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that the parasitism rate increased with parasitoid age and number. Tunca et al [51] evaluated the potential of O. kuvanae as a biocontrol agent for H. halys and observed that the highest parasitism rate occurred by 5 and 7-day-old parasitoids. In a study by Aung et al [52], the percentage parasitism and the number of progeny of O. nezarae when parasitising eggs of R. clavatus were significantly decreased in old females (20 days old).…”
Section: Discussionmentioning
confidence: 99%
“…Ooencyrtus kuvanae Howard (Hymenoptera: Encyrtidae) is an egg parasitoid that targets the spongy moth, Lymantria dispar Howard (Lepidoptera: Lymantriidae), as well as eggs of other insects such as the spotted lanternfly ( Brown 1984 , Liu and Mottern 2017 , Tunca et al 2017b , 2020 , Liu 2019a ). This parasitoid exhibits a haplodiploid reproductive strategy, typically laying 1 offspring per egg ( Somjee et al 2011 ), and may go through multiple generations while parasitizing a single egg mass of the spongy moth before exhausting its available hosts ( Brown et al 1982 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ooencyrtus kuvanae (Howard) (Hymenoptera: Encyrtidae) is a primary egg parasitoid of Lymantria dispar (L.) (Lepidoptera, Lymantriidae) (Howard, 1910; Tadic and Bincev, 1959; Brown, 1984; Hofstetter and Raffa, 1998; Wang et al ., 2013) but it can also parasitize other hosts, such as Dendrolimus spectabilis Butler (Lepidoptera: Lasiocampidae), Malacosoma americana (Fabricius), M. neustria tartacea (Motschulsky), Euproctis chrysorrhoea (Linnaeus), Hemerocampa leucostigma (Abbot & Smith), Hemerocampa definata (Packard), Lymantria fumida (Butler), Nygmia phaeorrhoea (Donovan), Stilpnotia salicis (Linnaeus) Eriogyna pyreterom (Westwood) (Lepidoptera: Saturniidae), Lycorma delicatula (White) (Hemiptera: Fulgoridae) and H. halys (Stål) (Hemiptera: Pentatomidae) (Huang and Noyes, 1994; Hofstetter and Raffa, 1998; Liu, 2019; Tunca et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%